Regional distribution of nosocomial infections due to ESBL-positive Enterobacteriaceae in Germany: data from the German National Reference Center for the Surveillance of Nosocomial Infections (KISS). (March 2015) - Leistner, R.; Schröder, C.; Geffers, C.; Breier, A.-C.; Gastmeier, P.; Behnke, M.
Abstract: Surveillance systems for hospital infections are reporting increasing rates of extended-spectrum β-lactamase (ESBL)-positive Enterobacteriaceae in Europe. We aimed to perform a national survey on this trend and on the regional distribution of nosocomial infections due to ESBL-positive Enterobacteriaceae in German hospitals. Data from 2007 to 2012 from two components of the German national nosocomial infection surveillance system were used for this analysis. The data derive from intensive care units and surgical departments. Independent factors determining the proportion of ESBL-positive Enterobacteriaceae among nosocomial infections due to Enterobacteriaceae and changes in its regional distribution (broken down into German federal states) were calculated by regression analysis. From 2007 to 2012, the data showed a significantly increasing proportion of ESBL-positive Enterobacteriaceae in surgical site infections (from 11.46 to 15.38, 134%, p 0.003), urinary tract infections (9.36 to 16.56, 177%, p <0.001) and lower respiratory tract infections (11.91 to 14.70, 123%, p <0.001) due to Enterobacteriaceae. Factors independently associated with a growing proportion were: Thuringia (p 0.009; odds ratio (OR) 1.53), North Rhine-Westphalia (p <0.001; OR 1.41) and general surgery ward (p 0.002; OR 1.47). The proportion of ESBL-positive Enterobacteriaceae in nosocomial infections has significantly increased in Germany over the last 6 years. Hospitals in Central Germany and surgical departments in all of Germany are especially affected by this development.